2015
DOI: 10.1017/s0022149x15000905
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of selected paramphistome isolates from cattle in southern Africa

Abstract: Paramphistomes are parasites of domestic and wild ruminants, the effects of which in animal health remain underestimated. Very few studies in Africa have been done using molecular techniques to resolve situations associated with taxonomical groupings and epidemiology of these parasites. In this study, the genetic variability of nine representative paramphistome isolates collected from southern African countries, namely Botswana, South Africa, Zambia and Zimbabwe, was assessed using both morphological and inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…1) by matching genetic sequences (<0•6% for ITS2 and <1•3% cox1) collected from cercariae and adults: (1) ITS2 sequences from cercariae from C. natalensis (GU735645) collected in Kenya grouped with sequences from adult worms we recovered from cattle (clade 2), provisionally identified as Carmyerius exporous (Dinnik and Dinnik, 1960). 2Cercariae (clade 4) we collected from C. natalensis matched adults collected in this study as well as two adults from Botswana (KP639636) and Kenya (GU735658) identified as Carmyerius dollfusi by Dube et al (2015). The latter species was synonymized with C. mancupatus (Sey, 1991), a species known to be transmitted by C. natalensis (Dinnik, 1965).…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…1) by matching genetic sequences (<0•6% for ITS2 and <1•3% cox1) collected from cercariae and adults: (1) ITS2 sequences from cercariae from C. natalensis (GU735645) collected in Kenya grouped with sequences from adult worms we recovered from cattle (clade 2), provisionally identified as Carmyerius exporous (Dinnik and Dinnik, 1960). 2Cercariae (clade 4) we collected from C. natalensis matched adults collected in this study as well as two adults from Botswana (KP639636) and Kenya (GU735658) identified as Carmyerius dollfusi by Dube et al (2015). The latter species was synonymized with C. mancupatus (Sey, 1991), a species known to be transmitted by C. natalensis (Dinnik, 1965).…”
Section: Discussionmentioning
confidence: 69%
“…The phylogenetic trees were useful, however, in providing preliminary hypotheses for how the various clades were related to one another (see the paragraph below). Relative to other paramphistomoid molecular phylogenetic studies involving specimens from African ruminants and snails, we recovered five out of the six previously reported taxa from Kenya, Egypt and Tanzania noted by Lotfy et al (2010), three of the three identified taxa from Zimbabwe, Zambia and Botswana (Dube et al 2015) and one of the two identified taxa from Algeria (Titi et al 2014). The extent of overlap among specimens recovered from all four studies suggests that at least some of the species have broad distributions in Africa.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations